TINGKAT PERILAKU PENGOBATAN, KEPATUHAN MINUM OBAT, DAN KADAR GULA DARAH PASIEN DIABETES MELLITUS RAWAT JALAN DI RSUD BRIGJEND. H. HASAN BASRY KANDANGAN - Novia Ariani; Riza Alfian; Erna Prihandiwati (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2022)
Diabetes mellitus is a metabolic disorder of the body that arises in a person because of an increase in blood sugar levels above the normal value. The case of diabetes mellitus in Indonesia is ranked 7th in the world with the number of patients as many as 8.5 million people. The level of treatment behavior, the level of medication adherence, and blood sugar levels is a critical determinant of the success of diabetes mellitus therapy.The research was conducted by using observational method. Sampling was done by consecutive sampling method. Samples meeting the inclusion criteria were 153 patients. The inclusion criteria in this study were DM patient in RSUD Brigjend. H. Hasan Basry Kandangan at the age of 18 - 65 years and willing to follow the research by filling informed consent first. Exclusion criteria were DM patients with deaf, illiterate, and recurrent patients. Data collection was done by filling out KAP-DM and MARS questionnaires, blood glucose data obtained from patient's medical records. The data of the research are presented in descriptive form using frequency distribution test.The results showed that the sample with preset treatment treatment rate was 22.2%; contemplation of 39.2%; preparation of 18.3%; and the action amounted to 20.3%. The results of drug adherence compliance analysis showed low adherence medication level of 2.0%, moderate 55.6% and high 42.4%. Blood sugar levels of controlled samples were 35.3% and uncontrolled were 64.7%.Based on the results of the study it can be concluded that the sample is dominated by the level of behavior of contemplative treatment, the level of medication adherence was medium, and uncontrolled blood sugar levels